Aesculus hippocastanum L.: A Simple Ornamental Plant or a Source of Compelling Molecules for Industry? - Asma Dridi; Filipa S. Reis; Tânia C. S. P. Pires; Ricardo C. Calhelha; Carla Pereira; Khalil Zaghdoudi; Isabel C. F. R. Ferreira; Lillian Barros; João C. M. Barreira (Separations, 2023)
Aesculus hippocastanum L., also known as horse chestnut, is an ornamental tree whose seeds are mostly discarded in landfills in the regions where they are grown. However, recent studies have shown that these seeds can be a source of interesting compounds for several industries. This work aimed to chemically characterize horse chestnut seeds at the level of compounds recognized for their wide bioactivity, i.e., organic acids, including phenolic compounds, using chromatographic methodologies (UFLC-DAD and LC-DAD-ESI/MSn). In addition, the bioactivity of these seeds was evaluated by in vitro methodologies, seeking to relate the respective (bio)activity to the compounds present in the endocarp (husk), seed coat (skin), and peeled seed (pulp). The antioxidant activity (lipid peroxidation inhibition and oxidative haemolysis inhibition), antibacterial potential (against Gram-positive and Gram-negative bacteria) and cytotoxicity (in human tumour cell lines and porcine liver primary cells) were evaluated. Kaempferol-O-pentoside-O-hexoside-O-hexoside was the main phenolic identified in the pulp. At the same time, (-)-epicatechin and β-type (epi)catechin dimer were the major phenolics present in husk and skin, respectively. In general, A. hippocastanum extracts presented antioxidant and antibacterial potential, without toxicity up to the maximal tested dose. Overall, these findings anticipate potential applications of A. hippocastanum seeds in food- or pharmaceutical-related uses.